The Effect of Political Connections and Board Gender Diversity on Tax Avoidance in Consumer Goods Firms - Ananda Pratiwi Rios Abas; Septy Indra Santoso; Mahardika Catur Putriwana Malik (Journal of International Conference Proceedings, 2025)
This study analyzes the impact of political connections and gender diversity on the board of directors toward tax avoidance in manufacturing firms in the consumer goods sector, with firm size as a moderating variable. The research used 25 firms listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Data were processed using multiple linear regression and Moderated Regression Analysis (MRA) with the EViews software. The findings reveal that political connections have a positive and significant effect on tax avoidance, while gender diversity on the board of directors appears no critical impact. Moreover, firm size does not moderate the relationship between political connections and tax avoidance, nor between gender diversity on the board of directors and tax avoidance. Future research is recommended to extend the observation period, expand the research objects across sectors, and include other independent variables that may influence corporate tax avoidance behavior